1989
DOI: 10.1042/bj2570831
|View full text |Cite
|
Sign up to set email alerts
|

C3 binds covalently to the Cγ3 domain of IgG immune aggregates during complement activation by the alternative pathway

Abstract: Ovalbumin-antiovalbumin IgG immune aggregates were incubated with normal human serum in the presence of iodo[1-14C]acetamide, in conditions in which only the alternative pathway of complement was activated. The [14C]C3b-IgG covalent complexes formed were digested with pepsin, and analysed by SDS/polyacrylamide-gel electrophoresis and fluorography. Covalent complexes of [14C]C3-Fd and [14C]C3-pFc' were visualized, demonstrating that, during complement activation by the alternative pathway, C3 is covalently inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…At the macromolecular level, the covalent binding of C3 to immune complexes had been studied. It was shown that C3b mainly bound to the antibodies (Gadd & Reid, 1981) and at multiple sites (Anton et al, 1989(Anton et al, , 1994. Using heat-aggregated IgG, obtained from a myeloma patient, Shohet et al (1993) showed that C3b, activated via the alternative pathway, bound to one major region of the heavy chain of IgG containing six potential acceptor sites, in the form of serine and threonine residues.…”
Section: Ska Law and Aw Doddsmentioning
confidence: 99%
“…At the macromolecular level, the covalent binding of C3 to immune complexes had been studied. It was shown that C3b mainly bound to the antibodies (Gadd & Reid, 1981) and at multiple sites (Anton et al, 1989(Anton et al, , 1994. Using heat-aggregated IgG, obtained from a myeloma patient, Shohet et al (1993) showed that C3b, activated via the alternative pathway, bound to one major region of the heavy chain of IgG containing six potential acceptor sites, in the form of serine and threonine residues.…”
Section: Ska Law and Aw Doddsmentioning
confidence: 99%
“…Clq purification and labeling. Clq was purified from NHS by high-pH precipitation, ion-exchange chromatography on BioRex 70, and gel filtration on Bio-Gel A5m (27, 45) as described previously (2). The purity of the isolated Clq was verified by polyacrylamide gel electrophoresis (PAGE).…”
mentioning
confidence: 99%
“…14 Because this complement-attenuating effect of IVIG might represent an important therapeutic effect in clinical applications where complement is involved in the pathogenic process, we addressed the question whether IVIG stimulated inactivation of C3b-containing complexes in vivo. C3b-containing complexes comprise a population of ester-linked complexes 14,[17][18][19][20][21][22] of which the most abundant ones carry 2 C3b and another plasma protein, primarily IgG. 14,17,21 We selected dermatomyositis (DM) for our studies because it is associated with complement activation beyond C3, with deposition of C5b to 9 to endomysial capillaries, 13 and patients may profit from high-dose IVIG treatment.…”
mentioning
confidence: 99%